Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/diagnostics10121074
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Calcification Factors and Endothelial-Dysfunction Factors on the Development of Unstable Atherosclerotic Plaques

Abstract: Background: This study aimed to evaluate changes in markers of calcification and of endothelial dysfunction during the development of calcification and instability of atherosclerotic plaques and to identify associations of calcification factors with the formation of unstable plaques. Methods: We analyzed 44 male patients with coronary atherosclerosis who underwent endarterectomy in coronary arteries during coronary bypass surgery. The endarterectomy material (intima/media) was examined using histological and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…The results of our study showed that a higher level of OPN concentration was present in patients whose atherosclerotic plaque was more stable on MRI (Type IV and V according to the AHA) [65]. Similar results have been reported by Polonskaya Y et al They showed that OPN levels are lower in unstable plaques in patients who undergo endarterectomy during coronary bypass surgery [66]. In turn, findings by Kadoglou et al suggest the notion that OPN down-regulates plaque calcification and may promote plaque instability as assessed by Gray-scale and color Doppler ultrasound examination [67].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study showed that a higher level of OPN concentration was present in patients whose atherosclerotic plaque was more stable on MRI (Type IV and V according to the AHA) [65]. Similar results have been reported by Polonskaya Y et al They showed that OPN levels are lower in unstable plaques in patients who undergo endarterectomy during coronary bypass surgery [66]. In turn, findings by Kadoglou et al suggest the notion that OPN down-regulates plaque calcification and may promote plaque instability as assessed by Gray-scale and color Doppler ultrasound examination [67].…”
Section: Discussionsupporting
confidence: 91%
“…Alexander Tacey and associates 38 30,40,41 Among patients undergoing coronary bypass surgery, their blood OCN concentrations correlated with OCN levels in coronary atherosclerotic plaques and were higher in patients with calcified coronary plaques; in addition, OCN content increased with the size of the calcification deposits in plaque. 42 Recent studies have reported that OCN-expressing endothelial progenitor cells may involve vessel stiffness; they are generated in the bone marrow and secreted into vascular regions impaired by ischemia or endothelial dysfunction and mediate abnormal repair. 43,44 In vivo rat model of vitamin D induced vascular calcification revealed a correlation between elevated OCN levels.…”
Section: Osteocalcin and Endothelial Functionmentioning
confidence: 99%
“…Apart from bones, OPN appears to be involved in vascular inflammation and atherosclerosis [67]. Several lines of evidence suggest that OPN promotes atherosclerotic plaque formation, leading to artery calcification [68][69][70]. In patients with CHD, OPN was found to be localized in calcified atherosclerotic lesions [59] and calcified cardiac valves [71].…”
Section: Osteopontinmentioning
confidence: 99%